Combined training is not superior to strength and aerobic training to mitigate cardiovascular risk in adult healthy men - Gonçalves, Reginaldo; Motta-Santos, Daisy; Szmuchrowski, Leszek; Couto, Bruno; M. Soares, Ytalo; de O. Damasceno, Vinícius; F. Pedrosa, Gustavo; D. M. Drummond, Marcos; V. Lima, Fernando; S. Silva, Alexandre (Biology of Sport, 2022)
Although the beneficial effects of aerobic training on cardiovascular risk factors are evident, the potential beneficial effect of strength and combined training on these risk factors is controversial. This study aimed to evaluate the effect of aerobic and strength training programmes, performed alone or in combination, on cardiovascular risk factors in sedentary, apparently healthy and non-obese adult men. The study was conducted with 37 subjects who were randomly divided into the following groups: aerobic (AG), combined (ASG), strength (SG) and control (CG). The exercise programmes were performed three times a week and lasted approximately 50 minutes. Dietary intake, anthropometry, blood pressure, muscular strength, aerobic capacity, lipid profile and glycaemic control were assessed before and after 12 weeks of the intervention. One-way analysis of variation (ANOVA) for baseline, and ANOVA for repeated measures were used to assess differences between the initial and final time points of the four groups. Changes in blood pressure and glycaemic control were not significant in any of the groups. No differences were observed in LDL-C between training groups. HDL-C increased significantly only in the AG. In conclusion, if minimal changes in the lipid profile are needed, an aerobic training programme can provide possible benefits for HDL-C in apparently healthy and non-obese adult men.